2014
DOI: 10.1016/j.urology.2014.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Supplementation and Urinary Oxalate Excretion in Normal Subjects on a Low-oxalate Diet

Abstract: OBJECTIVE To determine if fish oil supplementation reduces endogenous oxalate synthesis in healthy subjects. MATERIALS AND METHODS Fifteen healthy non–stone-forming adults participated in this study. Subjects first abstained from using vitamins, medications, or foods enriched in omega-3 fatty acids for 30 days. Next, they collected two 24-hour urine specimens while consuming a self-selected diet. Subjects consumed an extremely low-oxalate and normal-calcium diet for 5 days and collected 24-hour urine specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…They suggested that this inconsistency might be due to differences in their respective patient cohorts as their earlier study involved hypercalciuric patients while their subsequent study did not [5]. Interestingly, Table 1 shows that four of the other studies in which no decrease in urinary Ca occurred used healthy subjects as their test group as opposed to stone-formers [6,10,14,25] lending support to the notion that PUFA-induced reduction of Ca excretion is possibly restricted to stone-forming patients. Indeed, Buck and co-workers commented in an earlier paper that the normalizing effect of fish oil with respect to urinary calcium and oxalate levels was more pronounced in patients in whom these parameters were markedly raised [1].…”
Section: Pufa Dietary Interventionsmentioning
confidence: 96%
See 2 more Smart Citations
“…They suggested that this inconsistency might be due to differences in their respective patient cohorts as their earlier study involved hypercalciuric patients while their subsequent study did not [5]. Interestingly, Table 1 shows that four of the other studies in which no decrease in urinary Ca occurred used healthy subjects as their test group as opposed to stone-formers [6,10,14,25] lending support to the notion that PUFA-induced reduction of Ca excretion is possibly restricted to stone-forming patients. Indeed, Buck and co-workers commented in an earlier paper that the normalizing effect of fish oil with respect to urinary calcium and oxalate levels was more pronounced in patients in whom these parameters were markedly raised [1].…”
Section: Pufa Dietary Interventionsmentioning
confidence: 96%
“…We note that a total of 16 studies is listed. PUFAs which were tested are EPA (2 studies) [1,5], EPA+DHA (8 studies) [1,2,[6][7][8][9]11,14], LA+GLA (5 studies) [2,10,25], and EPA+DHA+GLA+LA (one study) [2]. These have been delivered as fish oil or as isolated supplements (EPA, GLA, evening primrose oil).…”
Section: Pufa Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated that the administration of a lactic acid bacterial probiotic reduced oxalate excretion in patients with idiopathic hyperoxaluria [31]; although this has not been substantiated by others [24]. The administration of fish oil should be further explored to confirm its effects and mode of action [32]. Pyridoxine therapy has been recommended for patients with hyperoxaluria.…”
Section: Other Strategies To Lower Urinary Oxalate Excretionmentioning
confidence: 99%
“…Споживання оксалатів у поєднання з жирами, наприклад риб'ячим жиром, не впливає на рівень їх екскреції. Проте викликає жваву дискусію у науковій спільноті, оскільки не підтверджує і не спростовує попередні результати досліджень, які описують підвищення ексретованого оксалату за умов високожирової дієти [17].…”
Section: леся вікторівнаunclassified